Men's mental health service engagement amidst the masculinity crisis: towards a reconstruction of traditional masculinity - Rita Hui Ting Lok; Yik Wa Law (SSM: Qualitative Research in Health)
Mental health service underutilisation amongst men is common in the developed world, and Hong Kong is no exception. Some have attributed the phenomenon to conformity to traditional masculinity. Global and local feminist movements and social processes/reforms leading to female advancement across arenas, however, are forcing men to rethink and adapt to new gender roles by “doing”, “re-doing” and “undoing” gender. In the current study, masculinity is considered not an entirely toxic or fixed concept but one that can be redefined or reconfigured to become a powerful approach by which service providers can engage and retain male service users. Guided by the health belief model (HBM), we conducted 21 semi-structured in-depth interviews with Hong Kong men aged 18-55. Most of the interviewees had a history of mental distress and suicide and/or self-harm ideation, and some of illicit drug addiction. These men commonly expressed feeling a sense of inadequacy when they encountered mental health problems and tended to utilise alternative coping approaches (e.g. substance use or self-harm) to avoid recognising their problems that required timely and appropriate professional intervention. They largely persisted in cultivating a sense of competency or agency through their ability to provide their families with both tangible and non-tangible support. The study results suggest the efficacy of taking men's unique masculine traits into account and formulating service design and engagement around three elements: (1) engaging potential male service users with purposes that go beyond their emotions/feelings alone; (2) articulating a programme with pragmatic steps and clear, observable and measurable/quantifiable outcomes; and (3) embracing, re-narrating and transforming negative masculinity narratives/beliefs into meaningful ones.